Reference ranges for serum periostin in a population without asthma or chronic obstructive pulmonary disease. Issue 10 (28th June 2016) - Caswell‐Smith, R.; Hosking, A.; Cripps, T.; Holweg, C.; Matthews, J.; Holliday, M.; Maillot, C.; Fingleton, J.; Weatherall, M.; Braithwaite, I.; Beasley, R.; ,
Summary: Background: The clinical utility of serum periostin as a type 2 biomarker in asthma is limited by lack of reference range values derived from a population without respiratory disease. Objective: To derive age‐ and sex‐related reference intervals for serum periostin from an adult population without asthma or COPD. Methods: Serum periostin levels were measured in 480 individuals, comprising 60 female and 60 male adults in each of the 18‐ to 30‐year, 31‐ to 45‐year, 46‐ to 60‐year and 61‐ to 75‐year age groups. Key exclusion criteria included a doctor's diagnosis of asthma, chronic bronchitis or COPD, and a history of wheezing or use of respiratory inhalers in the last 12 months. The distribution of periostin and logarithm‐transformed periostin levels was derived, and 90% confidence intervals for an individual prediction were calculated. Results: The distribution of serum periostin was right skewed with a mean (SD) periostin of 51.2 (11.9) ng/mL, median (IQR) 50.1 (43.1 to 56.9) ng/mL and range 28.1 to 136.4 ng/mL. There was no association between logarithm periostin and age or sex, although levels were low in current smokers. The 90% confidence limits for periostin were 35.0 and 71.1 ng/mL. Conclusions and Clinical Relevance: Serum periostin levels in adults without asthma or COPD are similar to those in adults with asthma. Serum periostin measurements do not need to be adjusted to take account of a patient's age or sex, although levels are lower in current smokers. Reference values for serum periostin levels in adults without asthma or COPD are provided.